1998
DOI: 10.1088/0953-2048/11/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural study of samples irradiated with rays at high doses

Abstract: We have investigated the damage induced by irradiation in silver added samples. The samples were prepared with 0 and 6.5 wt% of silver and irradiated by high-energy irradiation (50-150 Mrad). The roles of silver and dosage irradiation are discussed in terms of their effects on microstructure, crystallinity, critical temperature and zero-resistance temperature . After irradiation, decreased while the room-temperature electrical resistance increased by a factor of 8 for some of the samples. The difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 19 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…As discussed in the introduction, the regions of the grains are largely insensitive to γ-rays, while the regions of the grain boundaries of the polycrystalline HTSC material are expected to be very sensitive to γ-irradiation doses, causing either a net enhancement at low doses and might cause a net suppression of the transport properties (mostly at high doses). This result has been confirmed by experiments on HTSCs polycrystals [19] and crystals [34,35]. Thus, we may conclude that the major changes to the critical current density observed in our results are mainly due to the nature of the regions of the grain boundaries combined with their high sensitivity to γ-rays.…”
Section: Resultssupporting
confidence: 87%
“…As discussed in the introduction, the regions of the grains are largely insensitive to γ-rays, while the regions of the grain boundaries of the polycrystalline HTSC material are expected to be very sensitive to γ-irradiation doses, causing either a net enhancement at low doses and might cause a net suppression of the transport properties (mostly at high doses). This result has been confirmed by experiments on HTSCs polycrystals [19] and crystals [34,35]. Thus, we may conclude that the major changes to the critical current density observed in our results are mainly due to the nature of the regions of the grain boundaries combined with their high sensitivity to γ-rays.…”
Section: Resultssupporting
confidence: 87%
“…Second, the Compton electrons are produced by g-photons from some atoms and part of the energy will be imparted to the atoms by the momentum conversation [21]. g-Irradiation may also be evaluated that irradiation affects atomic structure of the alloy and g-irradiation is the reason for defects consisted in the structure [22]. The nominal displacement per atom (dpa) level was estimated as 1.03 Â 10 À 9 dpa.…”
Section: G-irradiatedmentioning
confidence: 99%
“…So, for a low silver concentration (YBC/Ag5), incorporation of Ag in the YBC structure can be considered according to Rangel et al 9 Silver atoms diffuse into the YBC structure, leading to the occupation of some Cu sites by Ag: the atomic Cu 2C radius (0.72Å) is very close to the Ag C radius (1.13Å). Therefore, incorporation of silver atoms would result in an increase in Cu 3C formal content, which corresponds to the increase of parameters (I s /I m and Cu 2p 2/Cu 2p 3 intensity ratio) obtained from our XPS measurements.…”
Section: Analysis Of Ybc/ag Compositesmentioning
confidence: 99%
“…5 -11 Most of the literature reported that Ag does not react with YBC whatever the temperature up to 960°C. 5 -7 Some works also suggested that Ag can occupy Cu sites in the YBC lattice 8,9 for a very low amount of silver. It must be mentioned that high-resolution interfacial studies using XPS or high-resolution transmission electronic microscopy (HRTEM) were carried out on thin films or crystals presenting a given orientation.…”
Section: Introductionmentioning
confidence: 99%